Spaceborne antennas for planetary exploration (Wiley-Interscience, 2006)
The book focuses on the radio frequency design and performance of antennas, but covers environmental and mechanical considerations as well. There is additionally a thorough treatment of all the analytical and measurement techniques used in design and performance assessment. Each chapter is written by one or more leading experts in the field of antenna technology